Does Training Matter? Exploring Police Officer Response to Domestic Dispute Calls before and after Training on Intimate Partner Violence - Ruff, Lanette (The Police Journal, 2012)
Police officers often leave the scene of many domestic dispute calls, unable to collect evidence needed to lay charges against the accused. They may find the residence in order, no visible signs of injury, and denial/refusal of all parties to provide statements to the police. Police officers may be called to respond to couples with repeated calls to emergency response, leaving without evidence on numerous occasions. As a result, many police officers may go to calls with preconceived notions about the risks and dynamics in intimate partner relationships, potentially impacting the kind of intervention used. Based on analysis of 1,032 domestic dispute files in Fredericton, NB, this paper explores police officer intervention before and after training on responding to intimate partner violence. It compares formal intervention, such as charges and arrests; collection of evidence, including written and oral statements from victim(s) and witness(es); and informal strategies used by police officers who respond to the scene of a domestic dispute, such as temporary separation of victim and accused, providing transportation to another residence, and contacting a shelter on behalf of the victim or accused.